(untitled) (Global Scientific Review, 2024)
The article analyzes such issues as types of families, in particular singleparent and large families, features of the family environment, the influence of the socio-psychological characteristics of the family on the processes of children’s perception of interpersonal relationships. In addition, the article uses methods of interviews, observation, scientific knowledge experiments, the self-assessment method (Sosnovsky modification), and methods of mathematical statistics. Scientific conclusions and recommendations obtained as a result of the study can be used as additional material in the publication of monographs, programs, teaching aids, as well as in the compilation of educational and methodological complexes in the disciplines of psychodiagnostics, family psychology and social psychology